Revealing disease‐specific endogenous target mimic of microRNA from long non‐coding RNA identification and characterization in Musa spp. - Audie Masola Putra; Husna Nugrahapraja; Fenny Martha Dwivany (Indonesian Journal of Biotechnology, 2023)
Banana (Musa spp.) is one of the most widely consumed fruits in the world. Unfortunately, the plants are at risk from many disease problems, which mainly derive from microorganism. It is a little known about the relationship between disease‐inducing microorganisms and plants, particularly at the molecular level. This research aimed to characterize long non‐coding RNA (lncRNA) from bananas that may have roles in regulating gene expression related to the disease response mechanism in banana derived from transcriptomic libraries. Furthermore, the detected transcripts were analyzed to identify the endogenous target mimics (eTMs) interaction between lncRNA and microRNA (miRNA) using computational approaches. Data from Cavendish banana (AAA group), Berangan (AAA group), Yunnan Banana (Itinerans), Dajiao (ABB group), and Klutuk (BB group) were used in this research. We found that lncRNA tends to be unsustainable, and most sizes are below 1000 bp (≥ 75%). Based on this result, we investigated the eTMs to determine lncRNA transcripts and miRNA, such as miR397 in Cavendish and miR444 in Klutuk. This transcript would be regulated following exposure to extreme temperatures and disease, indicating the possibility of disease‐specific interaction between bananas and their environment at the molecular level.